2020
DOI: 10.18203/2349-3291.ijcp20203639
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter closure of ventricular septal defect from retrograde transarterial approach: immediate and long-term outcome

Abstract: Background: Ventricular septal defect (VSD) is a commonly encountered congenital heart defect. The aim of this study was to analyze five years’ experience with patients who had undergone transcatheter closure of VSD using retrograde transarterial approach.Methods: It was a retrospective study conducted from December 2014 to December 2019. Cases planned for VSD closure in retrograde approach were included. A total of 147 cases fulfilled the criteria after left ventricular angiography and procedure was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The presence of hemodynamically significant PDA and VSD imposes a double threat of heart failure, and pulmonary hypertension to the patient. Recent studies showed excellent outcome in young infants after device closure [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of hemodynamically significant PDA and VSD imposes a double threat of heart failure, and pulmonary hypertension to the patient. Recent studies showed excellent outcome in young infants after device closure [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Closing VSD's with the Amplatzer muscular VSD device (MVSD) from AGA medical corporation was in practice since 90's. Multiple studies proved efficacy and excellent outcome of this method of closure [13][14][15][16][17][18] . Surgical closure of muscular VSD still poses some challenges because of course trabeculation on right ventricular side and difficult to localize from standard surgical approaches.…”
Section: Dscussionmentioning
confidence: 99%
“…Closure of muscular VSD specially in the apical septum needs cannulation of internal jugular vein, femoral arteries on both sides, general anesthesia and transoesophageal echocardiography guidance 13 .These are technically not feasible in young infants with weight equal or less than 5kg. Retrograde approach of closing perimembranous and muscular VSD's using Judkins guide catheter as delivery system is an established technique in our center, where multifunctional Konar-MFTM and ADO 11 from Abbot vascular device were used as closure device 14 . Konar-MF was found feasible, safe and effective in many studies [20][21][22] .…”
Section: Dscussionmentioning
confidence: 99%